Protestant Church Strategy in Building Spiritual Identity for Generation Alpha - Gultom, Joni Manumpak Parulian (Verbum Vitae, 2023)
This research aims to explain Protestant Church strategy in building Christian identity for Generation Alpha (Gen Alpha) amidst the adverse effects of globalization. Currently, the generation is navigating the complex terrain of a postmodern era characterized by the pervasive dissemination of concepts such as skepticism, subjectivism, and relativism. Gen Alpha has experienced a profound shift in cultural values, with a marked transition from religiosity to secularity. Consequently, Church must direct its attention towards the ideological and spiritual well-being of the generation. The influence of distortionary forces on the perception of reality is a matter of concern, stemming from various sources such as peers in the community, the educational system, social media, and the vast expanse of the Internet. The result show that Gen Alpha has been raised in the context of post-Christian and post-Church cultural environments. In this research, a qualitative research approach is used, predominantly through an extensive review of pertinent literature. The examination commences with an in-depth exploration of Gen Alpha and the formation of spiritual identity. Subsequently, the strategic initiatives conducted by Protestant Church are examined and the initiatives include worship services, fatherly mentorship, and cultivating a strong Christian identity. The conclusion shows the collaborative efforts of Church with the pastoral team, in the construction of its ministry. This is characterized by the implementation of transpersonal actions, the guiding of healing initiatives for the needs of families, and the cultivation of personalized spiritual practices. An important component of the comprehensive strategy includes the training and education of fathers to assume a central role in building the spiritual development of children. Furthermore, Church values the spiritual building of children aged between 4 and 14 years to fortify Christian identity.